Expert users` perceptions of racing wheelchair design and setup: the knowns, unknowns, and next steps - Bundon, A.; Mason, B. S.; Goosey-Tolfrey, V. L. (Adapted Physical Activity Quarterly, 2017)
This paper demonstrates how a qualitative methodology can be used to gain novel insights into the demands of wheelchair racing and the impact of particular racing chair configurations on optimal sport performance via engagement with expert users (wheelchair racers, coaches, and manufacturers). We specifically explore how expert users understand how wheels, tires, and bearings impact sport performance and how they engage, implement, or reject evidence-based research pertaining to these components. We identify areas where participants perceive there to be an immediate need for more research especially pertaining to the ability to make individualized recommendations for athletes. The findings from this project speak to the value of a qualitative research design for capturing the embodied knowledge of expert users and also make suggestions for "next step" projects pertaining to wheels, tires, and bearings drawn directly from the comments of participants.